Design and optimization of stamping process of ultra-thin stainless sheet into bidirectionally corrugated shape for finless high-efficiency heat exchanger. Issue 1 (2016) - Yanagimoto, Jun; Wake, Yasuhito; Zeise, Pascal; Mao, Hung; Shikazono, Naoki
Abstract: The stamping of an ultra-thin stainless steel sheet into a wave shape for a finless heat exchanger was investigated. As an alternative to fins made by the extrusion or drawing, a bidirectionally corrugated shape is advantageous because of its higher efficiency in heat exchange with smaller resistance to an ambient air flow. A greater wave height is advantageous, but is suppressed by fracture during stamping. A new stamping method was developed to realize a high-efficiency heat exchanger using an ultra-thin stainless steel sheet with an optimized corrugated shape in terms of the plan-view pattern and cross-sectional profile.